Ultrathin polymer biphase hydrogen separation membrane with porous structure as well as preparation method and application of ultrathin polymer biphase hydrogen separation membrane
By introducing porous structures and platinum particle catalysts into polymer hydrogen separation membranes, combined with coating and ion sputtering technology, ultra-thin films with high selectivity and high permeability are prepared, solving the permeability and selectivity of polymer films weigh the trade-offs and maintain long-term stable operation at high temperatures.
Patent Information
- Application Number
- CN202411683391.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing polymer hydrogen separation membranes are difficult to trade off between permeability and selectivity, and have insufficient stability, especially when operating at high temperatures.
Ultrathin polymer biphasic hydrogen separation membrane with porous structures is used to form a dense layer and a porous layer by introducing non-solvent porogenic agent and platinum particle catalyst into the matrix of polybenzimidazole and PEDOT:PSS, combining coating technology and Preparation by ion sputtering method achieves high selectivity and high permeability of the film.
It has 100% selectivity for hydrogen in a wide temperature range (room temperature to 300℃), which improves the permeability and selectivity of the traditional membrane. trade-offs.
Smart Images

Figure CN119186288A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen separation membrane preparation, and in particular to an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure, and a preparation method and application thereof. Background Art
[0002] At present, hydrogen energy, as a clean and efficient energy, has the characteristics of abundant sources, green and low carbon, and wide application, and plays an increasingly important role in promoting energy transformation. Since hydrogen cannot be directly mined in nature, it needs to be converted and processed from other energy sources.
[0003] At present, steam reforming of fossil energy is the main way to produce hydrogen. However, the hydrogen produced by this method contains a large amount of by-products, so hydrogen purification technology is an important link in the hydrogen energy industry chain. Compared with separation technologies such as low-temperature separation and selective adsorption, membrane separation has the advantages of flexible operation, high energy efficiency, environmental friendliness, and low operating cost. Among the many hydrogen separation membranes, polymer membranes have attracted widespread attention due to their low price, easy preparation and regulation, but there are trade-offs between permeability and selectivity and stability issues.
[0004] The patent with publication number CN118374045B discloses a polymer biphasic dense membrane for H2 separation. The organic membrane overcomes the disadvantage of poor selectivity of traditional organic membranes and can stably separate H2 at 100-300°C. However, the permeation flux of the membrane is low, which may be related to the excessive permeation and diffusion resistance caused by the large thickness of the membrane (about 60 microns). Based on this, it is very meaningful to develop a polymer membrane that can solve the trade-off and stability problems between H2 permeability and selectivity. Summary of the invention
[0005] In view of the above problems, the present invention provides an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure and a preparation method and application thereof. The hydrogen separation membrane prepared by the present invention has a dense layer thickness of 1-5 μm and has 100% selectivity for H2 in a wide temperature range (room temperature to 300°C) without humidity control. The trade-off between the permeability and selectivity of the polymer membrane to H2 is solved, and it can operate for a long time for 160 hours at a high temperature of 300°C.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure, which specifically comprises the following steps: S1: Using N,N-dimethylacetamide (DMAC), the polybenzimidazole (PBI) powder was heated and stirred overnight to dissolve to obtain a homogeneous polybenzimidazole solution; S2: Evenly disperse the organic solvent N,N-dimethylacetamide (DMAC), the non-solvent porogen dibutyl phthalate (DBP) and the poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PEDOT:PSS) powder, and then stir and disperse with the polybenzimidazole homogeneous solution of step S1 to synthesize a casting solution; The introduction of non-solvent dibutyl phthalate will destroy the thermodynamic equilibrium of the polybenzimidazole homogeneous solution, thereby causing the homogeneous polybenzimidazole solution to phase separate into a polymer-rich phase (non-solvent-poor phase) and a non-solvent-rich phase (polymer-poor phase).
[0007] S3: After ultrasonic defoaming treatment, the casting solution is prepared into a proton-electron mixed conductive layer by using coating technology and drying method; The polymer-rich phase formed after drying is solidified to form a porous skeleton, and on the side of the membrane away from the aluminum foil (the upper surface of the membrane after scraping), the solvent N,N-dimethylacetamide and the non-solvent dibutyl phthalate evaporate rapidly, and the concentration of the polymer polybenzimidazole increases rapidly, thereby increasing the viscosity of the membrane away from the aluminum foil, inhibiting phase separation, and forming a dense layer of the membrane (1-5μm thick).
[0008] S4: using a non-solvent induced phase separation method and a drying method, the proton-electron mixed conductive layer of step S3 is immersed in methanol at room temperature for a period of time and then vacuum dried to obtain a proton-electron mixed porous conductive layer (p-OPBI-PEDOT:PSS); The methanol was fully replaced with the non-solvent dibutyl phthalate in the proton-electron mixed conductive layer by soaking, thereby forming a porous layer of the membrane rich in polymer polybenzimidazole.
[0009] S5: Pt particle catalyst is loaded on both sides of the proton-electron mixed porous conductive layer, the interface between the porous layer and the dense layer, and the inner surface of the porous layer pores by ion sputtering to obtain an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure.
[0010] Furthermore, in the step S1, the ratio of polybenzimidazole (PBI) to organic solvent N,N-dimethylacetamide (DMAC) is 1 g:10 mL; and the temperature for heating and stirring is 50°C.
[0011] Furthermore, in the step S2, the casting liquid is prepared by adding N,N-dimethylacetamide and dibutyl phthalate to poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder, and ultrasonically dispersing it for 1 hour to obtain a mixture; placing the mixture in the polybenzimidazole homogeneous solution of step S1, continuing to heat and stir for 6 hours, and after being fully dispersed, cooling it to room temperature to obtain the casting liquid.
[0012] Furthermore, the mass ratio of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder, dibutyl phthalate and N,N-dimethylacetamide is 1:20:40, the mass ratio of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder and polybenzimidazole powder of step S1 is 1:10, and the temperature of heating and stirring is 80°C.
[0013] Furthermore, in step S3, the ultrasonic time is 30 minutes; the specific steps of preparing the proton-electron mixed conductive layer by the coating technology and drying method are as follows: S31: Lay clean aluminum foil flat on the automatic coating machine and vacuum it to make it flat; S32: pouring the casting solution onto the aluminum foil; S33: Set the film thickness and adjust the coating machine parameters; S34: placing the membrane in a clean environment; S35: The membrane is placed in a vacuum drying oven for drying to obtain a proton-electron mixed conductive layer.
[0014] Furthermore, in the step S33, the film thickness is 40-60 μm, and the scraping speed is 2 mm / s; in the step S34, the placement time is 3 hours; and in the step S35, the vacuum drying is performed at 100° C. for 10 hours.
[0015] Furthermore, in step S4, the immersion time in methanol is 24 hours, and the vacuum drying is performed at 80° C. for 24 hours.
[0016] Furthermore, in the step S5, Pt particle catalyst is loaded on both sides of the proton-electron mixed porous conductive layer, the junction of the porous layer and the dense layer, and the inner surface of the pores of the porous layer by ion sputtering, so that the Pt catalyst is distributed on both sides of the membrane, the junction of the porous layer and the dense layer, and the inner surface of the pores of the porous layer. Specifically, the proton-electron mixed porous conductive layer is cut using a circular mold and placed on the sample stage of the ion sputtering instrument, and the porous conductive layer is loaded with platinum particle catalyst, so that both sides of the membrane, the junction of the porous layer and the dense layer, and the inner surface of the pores of the porous layer are evenly loaded with platinum particle catalyst, so as to obtain an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure.
[0017] The present invention also provides an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure prepared by the above-mentioned preparation method, wherein the hydrogen separation membrane comprises a porous layer, a dense layer, and Pt particles loaded as catalysts on both sides of the membrane, at the junction of the porous layer and the dense layer, and on the inner surface of the pores of the porous layer, wherein the porous layer and the dense layer of the membrane together constitute a proton-electron mixed porous conductive layer (p-OPBI-PEDOT:PSS), which is composed of organic matter for transporting protons and polymer materials for conducting electricity.
[0018] The present invention also provides an application of the ultra-thin polymer two-phase hydrogen separation membrane with a porous structure, wherein the ultra-thin polymer two-phase hydrogen separation membrane with a porous structure is used for H2 separation.
[0019] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, a porous ultra-thin polymer two-phase hydrogen separation membrane with 100% selectivity for H2 is provided by improving the structure of the conventional dense membrane. Firstly, compared with the conventional organic H2 separation membrane, the porous ultra-thin polymer two-phase hydrogen separation membrane prepared by the present invention makes full use of organic matter to achieve H2 separation. + and e - The internal dual channels are constructed to achieve 100% selectivity for H2. Secondly, compared with the traditional dense membrane, the porous structure of the membrane in the present invention plays a dual role of effective support and reducing the thickness of the dense layer, and the introduction of the porous structure provides more proton and electron transmission channels. Finally, the porous layer of the present invention increases the contact area between hydrogen and the catalyst, thereby increasing the active sites of the catalyst Pt, and the ultra-thin dense layer reduces the mass transfer resistance of hydrogen permeation, improves the hydrogen permeation flux, and further solves the trade-off problem between permeability and selectivity, which not only ensures 100% selectivity of hydrogen, but also improves the hydrogen permeation flux. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The (a) front side, (b) cross section, and (c) back side of the real object scanning electron microscope representation of the hydrogen separation membrane of the present invention; Figure 2 It is a diagram of the mechanism of separation of H2 by the hydrogen separation membrane of the present invention; Figure 3 It is a diagram of the device for separating H2 using the hydrogen separation membrane of the present invention. DETAILED DESCRIPTION
[0021] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.
[0023] Example 1 This embodiment provides an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure. The surface image characterized by scanning electron microscopy is shown in the attached Figure 1 The mechanism diagram of H2 separation is shown in the attached Figure 2 , including a dense layer and a porous layer of a hydrogen separation membrane, and a catalytic layer composed of platinum particles on both sides of the membrane, at the junction of the porous layer and the dense layer, and on the inner surface of the pores of the porous layer; the ultra-thin polymer two-phase hydrogen separation membrane with a porous structure is used for H2 separation.
[0024] The method for preparing the ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure specifically comprises the following steps: S1: Weigh 0.5 g of polybenzimidazole powder (PBI) and add it into a beaker containing 5 mL of N,N-dimethylacetamide (DMAC) solvent. Place the beaker in an oil bath and heat it to 50°C. Stir at 300 r / min overnight until fully dissolved to obtain a homogeneous polybenzimidazole solution. S2: Weigh 0.05 g of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder (PEDOT:PSS) and add it to a beaker containing 1 mL of dibutyl phthalate (DBP) and 2 mL of N,N-dimethylacetamide (DMAC), place the beaker in an ultrasonic instrument, and treat it at 90 W for 1 hour to obtain a mixture; add the mixture to the homogeneous polybenzimidazole solution of step S1, continue to heat to 80°C, stir at 300 r / min for 6 hours, and after sufficient dispersion, cool it to room temperature to synthesize the casting solution.
[0025] The introduction of non-solvent dibutyl phthalate will destroy the thermodynamic equilibrium of the polybenzimidazole homogeneous solution, thereby causing the homogeneous polybenzimidazole solution to phase separate into a polymer-rich phase (non-solvent-poor phase) and a non-solvent-rich phase (polymer-poor phase).
[0026] S3: Place the beaker containing the casting solution into an ultrasonic instrument, perform 90W ultrasonic treatment for 30 minutes for defoaming treatment, and use coating technology and drying method to prepare the casting solution into a proton-electron mixed conductive layer. The specific steps are as follows: S31: Lay the clean cut aluminum foil paper flat on the automatic coating machine and vacuum treat it to make it flat; S32: pouring the degassing casting solution onto aluminum foil; S33: Set the film thickness (scraper size is 40-60μm), adjust the coating machine parameters (scraping speed is 2mm / s), and start the automatic coating machine; S34: placing the membrane in a clean environment for 3 hours; S35: The membrane is placed in a vacuum drying oven and dried at 100° C. for 10 h to obtain a proton-electron mixed conductive layer.
[0027] In step S35, the polymer-rich phase formed by drying is solidified to form a porous skeleton, and on the side of the membrane away from the aluminum foil (the upper surface of the membrane after film coating), the solvent N,N-dimethylacetamide and the non-solvent dibutyl phthalate evaporate rapidly, and the concentration of the polymer polybenzimidazole increases rapidly, thereby increasing the viscosity of the membrane away from the aluminum foil, inhibiting phase separation, and forming a dense layer of the membrane (1-5 μm thick).
[0028] S4: Use non-solvent induced phase separation and drying methods, specifically: place the proton-electron mixed conductive layer in a clean container at room temperature, pour anhydrous methanol into the container, and cover the proton-electron mixed conductive layer. Soak for 24 hours to allow methanol to fully replace the non-solvent dibutyl phthalate (DBP) in the proton-electron mixed conductive layer, thereby forming a porous layer of a membrane rich in polymer polybenzimidazole, and then vacuum dry it at 80°C for 24 hours to obtain a proton-electron mixed porous conductive layer (p-OPBI-PEDOT:PSS); S5: Pt particle catalyst is loaded on both sides of the proton-electron mixed porous conductive layer, the junction of the porous layer and the dense layer, and the inner surface of the pores of the porous layer by ion sputtering, so that the Pt catalyst is distributed on both sides of the membrane, the junction of the porous layer and the dense layer, and the inner surface of the pores of the porous layer. Specifically, the proton-electron mixed porous conductive layer is cut with a circular mold and placed on the sample stage of the ion sputtering instrument. The sputtering time is 3 min, the current is 20 mA, and the vacuum degree is 3.5 Pa. The porous conductive layer is loaded with platinum particle catalyst, so that both sides of the membrane, the junction of the porous layer and the dense layer, and the inner surface of the pores of the porous layer are evenly loaded with platinum particle catalyst, so as to obtain an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure.
[0029] The schematic diagram of the ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure for separating H2 in this embodiment is shown in the attached Figure 2 The principle of ultra-thin polymer dual-phase hydrogen separation membrane to separate hydrogen is: The catalyst Pt on the ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure dissociates hydrogen into hydrogen protons and electrons. Due to the concentration difference on both sides of the membrane, protons are conducted from the feed side of the membrane to the sweep side by proton hopping through the hydrogen bonds on the polybenzimidazole. Electrons are conducted through the continuous poly (3,4-ethylenedioxythiophene): polystyrene sulfonic acid formed in the membrane. Finally, the conducted protons and electrons recombine the hydrogen protons and electrons into hydrogen at the interface between the platinum particles on the outer surface of the dense layer and the organic phase, thus achieving hydrogen separation.
[0030] Experimental Example 1 The device diagram of ultra-thin polymer dual-phase hydrogen separation membrane with porous structure for separating H2 is attached. Figure 3The device consists of a homemade test device, a gas chromatograph, a horizontal tubular furnace, a ventilation line, a hydrogen separation membrane, a mass flow meter, and an exhaust gas treatment. The hydrogen separation membrane prepared in Example 1 is placed in the middle connection port of the homemade test device and sealed with sealing grease to ensure that the device is in a completely closed state. The test device is placed in a horizontal tubular furnace without heating. In this experiment, nitrogen is used as a mixed gas, 50% H2-50% N2 is passed into the feed side of the membrane, and inert gas argon is used as a purge gas to pass into the purge side of the membrane. The tail gas on the purge side is connected to a gas chromatograph for detection and analysis. The flow rates of H2 and N2 are 30mL▪min respectively. -1 , Ar flow rate: 60 mL / min -1 , the flow rate of each gas is controlled by a mass flow meter.
[0031] Experimental Example 2 The ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure prepared in Example 1 was used, and the reaction temperature was controlled by a horizontal tube furnace at 2 °C / min. -1 The heating rate was raised to 120° C., the mixed gas N 2 was replaced with CO 2 , and the remaining conditions were consistent with those in Experimental Example 1. The prepared hydrogen separation membrane was tested for its H 2 separation permeability performance.
[0032] Experimental Example 3 The ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure prepared in Example 1 was heated to 2 °C / min -1 The heating rate was increased to 260°C, the concentration of the conductive phase poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid was increased from 10% to 15%, and the other conditions were consistent with those in Experimental Example 1. The prepared hydrogen separation membrane was tested for its H2 separation permeability performance.
[0033] Experimental Example 4 The ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure prepared in Example 1 was heated at 2 °C / min -1 The heating rate was raised to 280° C., and the other conditions were consistent with those in Experimental Example 1. The prepared hydrogen separation membrane was tested for its H2 separation permeability performance.
[0034] Experimental Example 5 The ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure prepared in Example 1 was heated at 2 °C / min -1 When the heating rate was increased to 300°C and the other conditions were consistent with those in Experimental Example 1, the prepared hydrogen separation membrane was tested for its permeability performance of separating H2 for up to 160 hours.
[0035] Table 1 H2 permeation flux of Experimental Examples 1-5
[0036] The ultra-thin polymer two-phase hydrogen separation membrane with a porous structure prepared using this embodiment is applied to separate high-purity hydrogen. In Table 1, according to the results of Experimental Example 1, it can be found that the ultra-thin polymer two-phase hydrogen separation membrane with a porous structure has a good hydrogen permeation flux at room temperature, indicating that protons can be conducted through the hydrogen bonds of polybenzimidazole, and electrons can replace the external circuit and be conducted through poly (3,4-ethylenedioxythiophene): polystyrene sulfonic acid. According to the results in Table 1, it can be found that the permeation flux of hydrogen increases with the increase of temperature, indicating that the conduction of hydrogen is a thermally activated process. In addition, there is no gas other than hydrogen in the gas chromatogram, indicating that the present invention has 100% selectivity for hydrogen. According to the results of Experimental Example 5, it can be found that the hydrogen separation membrane can continue to operate stably for 160h at a high temperature of 300°C, indicating that the ultra-thin polymer two-phase hydrogen separation membrane with a porous structure has good thermal stability.
[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure, characterized in that: The specific steps include: S1: using N,N-dimethylacetamide to heat and stir the polybenzimidazole powder to dissolve it, so as to obtain a homogeneous polybenzimidazole solution; S2: Evenly disperse N,N-dimethylacetamide, dibutyl phthalate and poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder, and then stir and disperse with the polybenzimidazole homogeneous solution of step S1 to synthesize a casting solution; S3: After ultrasonic defoaming treatment, the casting solution is prepared into a proton-electron mixed conductive layer by using coating technology and drying method; S4: using a non-solvent induced phase separation method and a drying method, the proton-electron mixed conductive layer of step S3 is immersed in methanol at room temperature for a period of time and then vacuum dried to obtain a proton-electron mixed porous conductive layer; S5: Pt particle catalyst is loaded on both sides of the proton-electron mixed porous conductive layer, the interface between the porous layer and the dense layer, and the inner surface of the porous layer pores by ion sputtering to obtain an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure.
2. The method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure according to claim 1, characterized in that: In the step S1, the ratio of polybenzimidazole powder to N,N-dimethylacetamide is 1 g:10 mL; and the temperature for heating and stirring is 50°C.
3. The method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure according to claim 1, characterized in that: In the step S2, the casting liquid is prepared by adding N,N-dimethylacetamide and dibutyl phthalate to poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder, and ultrasonically dispersing for 1 hour to obtain a mixture; placing the mixture in the polybenzimidazole homogeneous solution of step S1, continuing to heat and stir, and after sufficient dispersion, cooling to room temperature to obtain the casting liquid.
4. The method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure according to claim 3, characterized in that: The mass ratio of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder, dibutyl phthalate and N,N-dimethylacetamide is 1:20:40, the mass ratio of poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid powder and polybenzimidazole powder of step S1 is 1:10, and the temperature of heating and stirring is 80°C.
5. The method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure according to claim 1, characterized in that: In step S3, the ultrasonic time is 30 minutes; the specific steps of preparing the proton-electron mixed conductive layer by the coating technology and drying method are as follows: S31: Lay clean aluminum foil flat on the automatic coating machine and vacuum it to make it flat; S32: pouring the casting solution onto the aluminum foil; S33: Set the film thickness and adjust the coating machine parameters; S34: placing the membrane in a clean environment; S35: The membrane is placed in a vacuum drying oven for drying to obtain a proton-electron mixed conductive layer.
6. The method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure according to claim 5, characterized in that: In the step S33, the film thickness is 40-60 μm, and the scraping speed is 2 mm / s; in the step S34, the placement time is 3 hours; in the step S35, the vacuum drying is performed at 100° C. for 10 hours.
7. The method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure according to claim 1, characterized in that: In the step S4, the immersion time in methanol is 24 hours, and the vacuum drying is performed at 80° C. for 24 hours.
8. The method for preparing an ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure according to claim 1, characterized in that: In the step S5, Pt particle catalyst is loaded on both sides of the membrane of the proton-electron mixed porous conductive layer, the interface between the porous layer and the dense layer, and the inner surface of the pores of the porous layer by an ion sputtering method. Specifically, the proton-electron mixed porous conductive layer is cut using a circular mold and placed on the sample stage of the ion sputtering instrument, and the porous conductive layer is loaded with platinum particle catalyst so that both sides of the membrane, the interface between the porous layer and the dense layer, and the inner surface of the pores of the porous layer are evenly loaded with platinum particle catalyst, thereby obtaining an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure.
9. An ultra-thin polymer two-phase hydrogen separation membrane with a porous structure prepared by the method for preparing an ultra-thin polymer two-phase hydrogen separation membrane with a porous structure as claimed in any one of claims 1 to 8.
10. An application of the ultra-thin polymer dual-phase hydrogen separation membrane with a porous structure as claimed in claim 9, characterized in that: The ultra-thin polymer two-phase hydrogen separation membrane with a porous structure is used for H2 separation.
Citation Information
Patent Citations
Solvent-resistant microporous polybenzimidazole membranes
CA2300519A1
Acid and alkali crosslinking proton exchange membrane and preparation thereof
CN102146204A
Proton-electron mixed conductive polymer two-phase dense membrane as well as preparation method and application of proton-electron mixed conductive polymer two-phase dense membrane
CN118374045A
Polybenzimidazole thin film composite membranes
US4933083A
Cited By
Hybrid hydrogen separation membrane filled with organic polymer by taking metal foam titanium as framework as well as preparation method and application of hybrid hydrogen separation membrane
CN122164249A
